2013
DOI: 10.1590/s1415-43662013000100003
|View full text |Cite
|
Sign up to set email alerts
|

Correlação entre a produtividade do feijoeiro no sistema de produção orgânica e atributos do solo

Abstract: Objetivou-se, com este trabalho, identificar um conjunto de atributos do solo, físicos (AF), químicos (AQ) e biológicos (AB) correlacionados com a produtividade do feijoeiro, visando estabelecer as condições de solo mais adequadas ao cultivo desta leguminosa no sistema de produção orgânica. Foram utilizados, conjuntamente, dados de dois experimentos instalados em novembro de 2003 com a cultivar Pérola, um em semeadura direta e outro em preparo convencional do solo, em Santo Antônio de Goiás, GO, em Latossolo V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
8

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 20 publications
0
5
0
8
Order By: Relevance
“…These results corroborate those of Cunha et al (2011), who observed a positive correlation between TOC and Cmic. High levels of Cmic reflect the presence of a high amount of active organic matter in the soil, which can maintain a high mineralization rate of plant residues (Stone et al, 2013). …”
Section: Resultsmentioning
confidence: 99%
“…These results corroborate those of Cunha et al (2011), who observed a positive correlation between TOC and Cmic. High levels of Cmic reflect the presence of a high amount of active organic matter in the soil, which can maintain a high mineralization rate of plant residues (Stone et al, 2013). …”
Section: Resultsmentioning
confidence: 99%
“…O feijoeiro comum é a espécie mais cultivada no mundo entre as demais do gênero Phaseolus, sendo conduzida aproximadamente por dois milhões de produtores dispersos no País, com 64% da produção envolvendo a agricultura familiar em estratos de área inferiores a cinco hectares (STONE et al, 2013).…”
Section: Introductionunclassified
“…The common bean (Phaseolus vulgaris L.) stands out among the agricultural crops in Brazil as a result of the extension of cultivated area, production value and importance as a source of protein for the population (TOLEDO et al, 2009). Bean is cultivated by approximately 2 million Brazilian farmers, being small farmers responsible for 64% of production in areas smaller than 5 hectares (STONE et al, 2013).…”
Section: Introductionmentioning
confidence: 99%